2019
DOI: 10.1111/jcmm.14825
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells exhaustion induced by myeloid‐derived suppressor cells in myelodysplastic syndromes patients might be through TIM3/Gal‐9 pathway

Abstract: CD8+ T cells play a central role in antitumour immunity, which often exhibit ‘exhaustion’ in the setting of malignancy and chronic viral infection due to T cell immunoglobulin and mucin domain 3 (TIM3) and myeloid‐derived suppressor cells (MDSCs). Our team previously found that overactive MDSCs and exhausted TIM3+CD8+ T cells were observed in myelodysplastic syndromes (MDS) patients. However, it is not obvious whether MDSCs suppress CD8+ T cells through TIM3/Gal‐9 pathway. Here, Gal‐9, as the ligand of TIM3, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“… 3 , 6 Our previous research found that MDSCs from MDS have obvious inhibition on CD8 + T cells in vitro . 36 Here, we found that the number of CD8 + T cells decreased, and the number of CD4 + T cells increased in MDS when MDSC expressed a higher TGF-β/TNF-α mRNA ratio. This result further demonstrated that MDSC had an inhibitory effect on CD8 + T cells, and the inhibition of MDSCs might depend on the TGF-β/TNF-α ratio.…”
Section: Discussionmentioning
confidence: 52%
“… 3 , 6 Our previous research found that MDSCs from MDS have obvious inhibition on CD8 + T cells in vitro . 36 Here, we found that the number of CD8 + T cells decreased, and the number of CD4 + T cells increased in MDS when MDSC expressed a higher TGF-β/TNF-α mRNA ratio. This result further demonstrated that MDSC had an inhibitory effect on CD8 + T cells, and the inhibition of MDSCs might depend on the TGF-β/TNF-α ratio.…”
Section: Discussionmentioning
confidence: 52%
“…Supporting this notion, it has been reported that IL-17 triggers the recruitment of CD11b + Gr-1 + MDSCs to mediate CD8 + T cell exhaustion in hepatitis B virus infection 44 and the CD11b + Gr-1 + MDSCs have been suggested to promote CD8 + T cell exhaustion through Tim-3/Galectin-9 pathway in myelodysplastic syndromes. 45 Given the role of IL-17RA signaling in CD8 + T cell survival and dysfunction in parasite infection; however, we do not rule out the direct effect of IL-17 on CD8 + TIL exhaustion. 46 Further studies are needed to elucidate the detailed cellular and molecular mechanisms by which IL-17-producing cells exert CD8 + T cell exhaustion.…”
Section: Discussionmentioning
confidence: 85%
“…In the TME, TIM3 mainly mediates T cell apoptosis and participates in tumor immunosuppression, and occurrence and development of tumors. TIM3 has four types of ligands, including carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), high-mobility group box 1 (HMGB1), phosphatidylserine (PtdSer), and Galectin-9 (Gal-9) ( Tao et al, 2020 ). Gal-9 was the first ligand to be identified, and its binding with TIM3 inhibits the T cell immune response and induces tumorigenesis.Tumor growth rates were significantly increased in TIM3-overexpressing EL4 mice ( Nakajima et al, 2019 ).…”
Section: Survey Methodologymentioning
confidence: 99%